RNA in situ hybridization of Escherichia coli in equine endometrial biopsies - Tukia, Elina; Hallman, Isa; Penttilä, Maarit; Hänninen, Satu; Kareskoski, Maria (Frontiers in Veterinary Science, 2023)
Endometritis is one of the major causes of infertility in mares. Escherichia coli and β -haemolytic streptococci are among the bacterial species most frequently isolated from the equine uterus. Some bacteria such as β-hemolytic streptococci, can persist in dormant forms and cause prolonged, latent or recurrent infections. Dormant bacteria may be present despite negative bacterial cultures, and they are resistant to antimicrobial treatment due to their resting metabolic state. The purpose of this study was to study formalin-fixed paraffin-embedded equine endometrial biopsies for the presence and localization of E. coli –bacteria, with a chromogenic RNAscope®-method for detection of E. coli-related 16S ribosomal RNA. Hematoxylin-eosin –stained endometrial biopsies were evaluated to determine the level of inflammation and degeneration. During estrus, samples were taken for endometrial culture and cytology with a double-guarded uterine swab. The samples included eight samples with moderate to severe endometrial inflammation detected in endometrial histopathology, and growth of E. coli in bacterial culture, six samples with moderate to severe endometrial inflammation but negative bacterial culture, and five samples with no endometrial pathology (grade I endometrial biopsy, negative endometrial culture and cytology) serving as controls. Positive and negative control probes were included in the RNA in situ hybridization, and results were confirmed with a fluorescence detection method (fluorescence in situ hybridization). Only unspecific signals of limited size and frequency of occurrence were detected in all samples, with random localization in the endometrium. No samples contained rod-shaped signals corresponding to bacterial findings. In conclusion, there was no evidence of bacterial invasion in the endometrium regardless of the inflammatory status of the biopsy or previous bacterial culture results. According to these findings on a small number of samples, invasion of E. coli is not a common finding in the lamina propria of mares, but these bacteria may also evade detection due to localized foci of infections, or supra-epithelial localization under the cover of biofilm. These bacteria and biofilm covering the epithelium may also be lost during formalin-fixation and processing.